O gênero hino na perspectiva baktiniana : uma abordagem dialógica do hino do MST e de outros enunciados concretos - Moraes, Flavio Henrique (Universidade Federal de São Carlos, 2015)
This study aims to understand the song genre from the perspective of Bakhtin (2010) and dialogical relations that it establishes with its fields or social spheres in which arises and manifests. We will take as objects of study two hymns of contemporary social movements and a statement chanted during Marches July 2013 namely: the Anthem of the Landless Rural Workers (MST), the Hymn of the Zapatista Movement and the statement concrete "Come To street ". Mirando such objects and articulating the concept of gender in the theoretical orbit circle which was part Bakhtin, I want to understand how is the transition from primary to secondary and genres such as the hymn, through its expressiveness, brand valuation of part of the story Movement embodied in the narrative of militants Settlement Monte Alegre, located in the region of Araraquara-SP, thus indicating the passage of the ethical to the aesthetic field.
Keywords: Analise do discurso; Gênero do discurso; Hino; Enunciado concreto; Círculo de Bakhtin; Speech genres; Anthem; Set out concrete; Bakhtin Circle; Intonation and expression; LINGUISTICA, LETRAS E ARTES::LINGUISTICA; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::FISIOLOGIA DA LINGUAGEM